Converting Advocacy to Action: #WakingTheFeminists Legacy - Dawe, Olwen (Irish Journal of Arts Management and Cultural Policy, 2020)
This piece explores the catalytic effect of the voluntary #WakingtheFeminists movement, sparked in late 2015 by the announcement of the Abbey Theatre’s ‘Waking the Nation’ 2016 commemorative centenary programme. In late 2015, gender inequality in Irish theatre came centre-stage, following the public announcement of the Abbey Theatre’s ‘Waking the Nation’ 2016 commemorative centenary programme. As the Irish state’s national theatre, this announcement was intended as a commemoration of one hundred years since the founding through uprising of the Irish state and thus symbolic of the state of contemporary Irish theatre. Featuring just one play written by a female playwright (and few other female creatives), its announcement triggered an online debate on social media. This moment catalysed a far wider debate. Here, Olwen Dawe reflects on a moment that gave rise to a movement, and how a voluntary group of artists and practitioners mobilised and strategised, garnering substantial engagement from the theatre community, policymakers and media, and developing a nationwide (and international) following in the process. In addition, she tracks the impact of #WakingTheFeminist’s advocacy campaign for gender equality in theatre, almost five years since the inception of the movement and as the deadline approaches of its target: 50:50 by November 2020.